Динаміка видової та просторової структури прибережних ландшафтних насаджень великого ставу дендропарку “Тростянець” - Ilyenko, A.A.; Medvedev, V.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
The results of studying of landscape compositions, the dynamics of number, the specific composition and spatial structure of the wood plantings of coastal area of Bolshoy prud for the period of 1948–2007 years are presented.